Synthesis of transition metal complexes containing symmetrical chalcone-derived Schiff bases and cytotoxic studies against bladder cancer cells - Tawfeeq, Nabeel Arif (2019)
Dithiocarbazate Schiff bases and their derivatives have drawn considerable attention due to their unique properties and applications. Many dithiocarbazate metal complexes have been synthesised and applied in many applications such as antibacterial, antifungal, antioxidant agents and in catalysis. Dithiocarbazate metal complexes have also shown significant cytotoxicity against many types of cancer cell lines. This study aims to synthesise non-toxic compounds by synthesising para substituted chalcone derivatives and studying the effect of substituted functional group electronegativity on the cytotoxicity of the metal complexes. Nine chalcones were synthesised using basecatalysed Aldol condensation. The chalcones were symmetrical in order to direct the electron density towards the transition metal in the complexes. These symmetrical chalcones were then reacted with S-benzyldithiocarbazate to form nine novel Schiff bases. A total of 45 novel metal complexes were synthesised by reacting these nine Schiff bases with five divalent transition metal acetates which were Ni2+, Fe2+, Cu2+, Zn2+ and Cd2+. +. These Schiff bases and their metal complexes were fully characterised using various characterisation techniques including FTIR, UV-Vis, 1H and 13C NMR spectroscopy, mass spectral, elemental analysis, and single crystal X-ray diffraction. The cytotoxic properties of these compounds were also tested against two types of bladder cancer cell lines which were the minimum-invasive human bladder cancer carcinoma cell line (RT112) and the invasive human bladder carcinoma cell line (EJ28).All Schiff bases were inactive against both types of bladder cancer cell. The unsubstituted chalcones and their metal complexes were inactive against both cells which means the substituted group on benzene ring plays an important roles toward the cytotoxicity of metal complexes. Cu(II) complexes of DTASB, DEASB, DIPASB, DCLASB, DBRASB, DNNMASB and DMeOSB showed moderate cytotoxicity against both cell lines with more selectivity toward EJ-28 than RT-112. Less than that, Zn(II) complexes of DTASB, DEASB and DIPASB showed moderate activity against bladder cancer cell line type EJ-28 while they were inactive against RT-112 cell lines. An Fe(II) complex, FeDMeOSB, showed moderate activity against both cell lines. CuDMeOSB showed highest cytotoxicity against both types of bladder cancer cell lines EJ-28 and RT-112 with IC50 values equal to 1.651 and 1.762 µM, respectively.In addition, CuDNNMASB showed more selectivity against RT-112 than EJ-28 with IC50 value equal to 1.874 µM.